Pengaruh Pendidikan dan Prestasi Kerja terhadap Pengembangan Karir pada Karyawan Koperasi Keluarga Besar PT. Semen Padang - Susanto, Perengki; Sari, Rina Devita (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2013)
This study aims to analyze: (1) The effect of education on career development, (2) influence job performance to career development. This research was conducted at the Family Cooperative PT.Semen Padang (KKSP) and the population of this study was all employees of the Family Cooperative PT.Semen Padang numbered 65 people. The sampling technique of this study was stratified sampling technique that is commonly used when the population consists of array groups stratified, and then the number of samples is 56 employees. To obtain a valid and reliable instrument to test the validity and reliability testing. The primary data in this study were obtained from the distribution of questionnaires to the respondents, while secondary data is data associated with the object of the research presented by the Family Cooperative Big PT. Semen Padang. The data analysis technique used is multiple regressions with SPSS version 16.00. The results showed that: (1) there is no significant effect of education on career development, (2) there is a significant effect of job performance on career development. Based on the discussion and conclusions, it is advisable to pay attention to the leadership aspects of education and job performance in order to enhance the career development of employees Cooperative Family of PT.Semen Padang.